Cultural Appropriation of Asian Cuisines in Western Chefs’ Cooking Videos: An Audience Reception - Mochammad Ferry Subagya; Pratiwi Retnaningdyah (Journal of Language and Literature, 2022)
The globalization era eliminates borders between cultures, making people mistakenly know cultural appropriation with cultural appreciation when recreating or adopting specific cultures outside their own. Examples of cultural appropriation are seen in Uncle Roger's reactional videos of the five western chefs recreating Asian dishes inaccurately. This study intends to improve the awareness of cultural appropriation by communicating cultural appropriation characteristics through videos and unveiling the harmful effects of cultural appropriation on the targeted culture. This study uses multimodal analysis to discover the inaccurate elements in the cooking videos and audience reception analysis to show audience response to cultural appropriation and its harmful effect based on James O. Young's cultural appropriation theory. The findings highlight three main elements that are presented inaccurately in the videos: (1) the kitchen utensils, (2) ingredients and seasonings, and (3) the cooking method. Spotlighting the inappropriate representation of Asian food by the five western chefs attracts massive protests toward them led by Uncle Roger. There are numerous responses from netizens who agree with Uncle Roger about the inaccurate food adaptation and find the harmful effect of cultural appropriation that gives misrecognition and bad stereotypes of Asian cuisine. Based on the previous response, the cooking videos by five western chefs are also classified as cultural exploitation because they received massive engagement and did not plan to revise their recipes.